Heads or tails: staged diversification in vertebrate evolutionary radiations. - Sallan, L; Friedman, M (2012)
Adaptive radiations, bouts of morphological divergence coupled with taxonomic proliferation, underpin biodiversity. The most widespread model of radiations assumes a single round, or 'early burst', of elevated phenotypic divergence followed by a decline in rates of change or even stasis. A vertebrate-specific model proposes separate stages: initial divergence in postcranial traits related to habitat use, followed by diversification in cranial morphology linked to trophic demands. However, there is little empirical evidence for either hypothesis. Here, we show that, contrary to both models, separate large-scale radiations of actinopterygian fishes proceeded through distinct cranial and later postcranial stages of morphological diversification. Early actinopterygians and acanthomorph teleosts dispersed in cranial morphospace immediately following the end-Devonian extinction and the Cretaceous origin of the acanthomorph clade, respectively. Significant increases in postcranial morphological variation do not occur until one interval after cranial diversification commenced. Therefore, our results question the universality of the 'general vertebrate model'. Based on the results of model-fitting exercises and application of the divergence order test, we find little evidence that the early onset of cranial diversification in these two radiations is due to elevated rates of cranial change relative to postcranial change early in their evolutionary histories. Instead, postcranial and cranial patterns are best fit by an Ornstein-Uhlenbeck model, which is characterized by constant evolutionary rates coupled with a strong central tendency. Other groups have been reported to show early saturation of cranial morphospace or tropic roles early in their histories, but it is unclear whether these patterns are attributable to dynamics similar to those inferred for our two model radiations.